Protagonismo da criança na construção dos seus significados sobre a música - Nascimento, Letícia Damasceno do (2019)
This research aims to understand children's perceptions and interactions about music lessons in a dedicated music school and a primary school. To achieve this, two places were chosen for empirical field work. The first place, the Artistic Initiation Course - CIART, is a community extension program in the School of Music at the Federal University of Rio Grande do Norte - EMUFRN. The second is an elementary school, Alegria Colégio e Curso, located in the city of Natal-RN. The work is based on studies and authors from early childhood education and childhood education and sociology. An inquiry was made to promote discourse with the authors in emphasizing children-centered explanations. This was fundamental for expression of the contributions and understandings about music-making in these two environments. These opinions and direct participation in the research were central to this work. To this end, the methodology is via a qualitative approach and uses participant class observation and parent questionnaires as data collection techniques. In addition, this research made use of the “conversation circle”. This was the main way to collect the data found to deal with the children researched in the two contexts of music teaching. Highlighting the research results, we see the direct relation of the context with the way to make music; the interaction between the children and their responses to the detriment of the activities performed during the conversation circles and the constant influence of the parents of the children. This work seeks not only to explain and investigate musical practice in childhood, but together with the children, to understand their impressions about music learning in an elementary and dedicated music school setting.